Effectiveness of the Implementation of the Ship Inspection Report Programme (SIRE) in Improving Ship Safety at PT Pertamina International Shipping - Tri Ambaryani, Dewi; Firzah, Muhammad (Journal Research of Social Science, Economics, and Management, 2025)
The adoption of the Ship Inspection Report Programme (SIRE) by PT Pertamina International Shipping demonstrates the company’s commitment to enhancing maritime safety and adhering to international standards set by the OCIMF. In practice, however, its implementation encounters several obstacles, including limited assimilation of program objectives, insufficient resources, and less-than-optimal internal communication and safety culture. This research evaluates the effectiveness of SIRE implementation across five dimensions of organizational effectiveness: clarity of goals, efficiency in resource utilization, organizational characteristics, internal communication, and adaptability to change. A descriptive qualitative method was applied, using purposive sampling to select five key informants directly involved in the program, with data gathered through in-depth interviews and analyzed thematically. The results indicate that although SIRE has been implemented effectively overall, significant challenges remain, particularly the lack of comprehensive understanding of its core purpose, as it is often viewed only as a vetting preparation tool. Other issues include the limited number of internal inspectors, weak inter-unit coordination and communication, and the absence of an adaptive roadmap to anticipate regulatory developments and external risks. To ensure sustained effectiveness, this study suggests enhancing case-based training, digitizing the inspection system, forming cross-functional teams, and formulating risk-based adaptive strategies.